Informe preliminar sobre la aceptación de BAT 1297 en la zona cafetera de Caldas - Hall Starbird, E; Pachico, Douglas H. (International Center for Tropical Agriculture, 1985)
Forty-four surveys were conducted on farmers growing the bean variety BAT 1297 in the department of Caldas, Colombia, and on prices in Mercaldas in the city of Manizales. This variety was found to very profitable when planted in association with coffee (both with and without agrochemicals) or with cassava, and in monoculture. Most farmers (76 percent) were satisfied with its yields, ranging between 25 and 29 kg per kilo of seed. `BAT 1297` accounted for 40 percent of the market in Mercaldas, that is, more than any other variety. The study indicated that 86 percent of farmers will continue to plant `BAT 1297` if the market is guaranteed, but only 14 percent would plant it for personal consumption. Among the reasons stated by farmers for planting `BAT 1297`, 35 percent were taking advantage of the ratoon of the coffee crop; 20 percent planted it as a trial; 16 percent because of a recommendation from FEDECAFE, and 14 percent because it fixes nitrogen. More than half of the farmers (53 percent) reported problems with pests and diseases